2022
DOI: 10.2147/jpr.s359220
|View full text |Cite
|
Sign up to set email alerts
|

Objective and Quantitative Evaluation of Spontaneous Pain-Like Behaviors Using Dynamic Weight-Bearing System in Mouse Models of Postsurgical Pain

Abstract: Background The paucity of objective and reliable measurements of pain-like behaviors has impeded the translatability of mouse models of postsurgical pain. The advanced dynamic weight-bearing (DWB) system enables evaluation of spontaneous pain-like behaviors in pain models. This study investigated the suitability and efficiency of the DWB system for assessing spontaneous pain-like behaviors and analgesic therapies in murine models of postsurgical pain. Methods Male adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Though only male mice were used, our study provides a proof-of-concept methodology for future studies using ADWB. Additional work will be necessary to further demonstrate the utility of ADWB in detecting and evaluating analgesic effects of currently available therapeutics 30 and/or testing preclinical TRPA1 inhibitors. 69 However, others have shown that this system can detect changes in response to drugs such as diclofenac, indomethacin, and celecoxib in various models of acute and chronic pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though only male mice were used, our study provides a proof-of-concept methodology for future studies using ADWB. Additional work will be necessary to further demonstrate the utility of ADWB in detecting and evaluating analgesic effects of currently available therapeutics 30 and/or testing preclinical TRPA1 inhibitors. 69 However, others have shown that this system can detect changes in response to drugs such as diclofenac, indomethacin, and celecoxib in various models of acute and chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…The ADWB allows for (1) the animal to freely explore its environment, facilitating the study of behavioral responses to nonreflexive mechanical hypersensitivity, 28 and (2) the objective measurement of both paw weight and surface area, eliminating bias in the data collection process. To date, this tool has been used to study a range of pain conditions (e.g., postoperative pain, 29 , 30 cancer-induced bone pain, 31 inflammatory hyperalgesia, 32 neuropathic pain, 33 , 34 and osteo- and inflammatory arthritis) 35 , 36 as well as neurological diseases including vestibulopathy 37 and multiple sclerosis. 38 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous limb pain-like behaviors were assessed using an advanced DWB apparatus (Bioseb, Vitrolles, Provence-Alpes-Côte D’Azur, France; catalog number: BIO-DWB-M), wherein changes in the postural equilibrium of each freely moving animal were tracked and analyzed. 20 The animal was placed in a transparent enclosure for 1 min for acclimatization, followed by a 5-min recording. A matrix comprising pressure sensors capturing the weight distribution data of each of the four paws was embedded in the floor.…”
Section: Methodsmentioning
confidence: 99%
“…18 Stimulus-evoked responses, such as the von Frey test, have been widely used in pain research to assess pain-related behavior. However, we selected DWB in this study because asymmetric weight distribution partially reflects spontaneous pain during free walking in unilateral paw pain models, [25][26][27] which appears to be more relevant and clinically important for assessing our novel JR model.…”
Section: Postoperative Assessments Behavioral Assessmentsmentioning
confidence: 99%